Perfect 2-colorings of the generalized Petersen graph GP(n,3) - Hamed Karami (Electronic Journal of Graph Theory and Applications (EJGTA), 2022)
In this paper we enumerate the parameter matrices of all perfect 2-colorings of the generalized Petersen graphs GP(n, 3), where n ≥ 7. We also give some basic results for GP(n, k).